Pellino1-mediated TGF-β1 synthesis contributes to mechanical stress induced cardiac fibroblast activation. (February 2015) - Song, Juan; Zhu, Yun; Li, Jiantao; Liu, Jiahao; Gao, Yun; Ha, Tuanzhu; Que, Linli; Liu, Li; Zhu, Guoqing; Chen, Qi; Xu, Yong; Li, Chuanfu; et al.
Abstract: Activation of cardiac fibroblasts is a key event in the progression of cardiac fibrosis that leads to heart failure. However, the molecular mechanisms underlying mechanical stress-induced cardiac fibroblast activation are complex and poorly understood. This study demonstrates that Pellino1, an E3 ubiquitin ligase, was activated in vivo in pressure overloaded rat hearts and in cultured neonatal rat cardiac fibroblasts (NRCFs) exposed to mechanical stretch in vitro . Suppression of the expression and activity of Pellino1 by adenovirus-mediated delivery of shPellino1 (adv-shpeli1) attenuated pressure overload-induced cardiac dysfunction and cardiac hypertrophy and decreased cardiac fibrosis in rat hearts. Transfection of adv-shpeli1 also significantly attenuated mechanical stress-induced proliferation, differentiation and collagen synthesis in NRCFs. Pellino1 silencing also abrogated mechanical stretch-induced polyubiquitination of tumor necrosis factor-alpha receptor association factor-6 (TRAF6) and receptor-interacting protein 1 (RIP1) and consequently decreased the DNA binding activity of nuclear factor-kappa B (NF-κB) in NRCFs. In addition, Pellino1 silencing prevented stretch-induced activation of p38 and activator protein 1 (AP-1) binding activity in NRCFs. Chromatin Immunoprecipitation (ChIP) and luciferase reporter assays showed that Pellino1 silencing prevented the binding of NF-κB and AP-1 to the promoter region of transforming growth factor-β1 (TGF-β1) thus dampening TGF-β1 transactivation. Our data reveal a previously unrecognized role of Pellino1 in extracellular matrix deposition and cardiac fibroblast activation in response to mechanical stress and provides a novel target for treatment of cardiac fibrosis and heart failure. Highlights: Pellino1 contributes to myocardial fibrosis following pressure overload. Pellino1 mediates mechanical stress induced cardiac fibroblast activation. Pellino1 regulates ubiquitination-dependent NF-κB activation in cardiac fibroblast. Pellino1 regulates mechanical stretch-induced activation of p38/MAPKs and AP-1. Pellino1 regulates fibrogenesis of cardiac fibroblast by inducing TGF-β1 synthesis.